EDITORIAL AUTOMATION: THE PURSUIT OF JOURNALISTIC MEANING IN AUTOMATED TOOLS AND AUTOMATED DECISION-MAKING SYSTEMS IN AUSTRALIAN NEWSROOMS - Montaña-Niño, Silvia (AoIR Selected Papers of Internet Research, 2023)
The panorama of editorial automation is moving at a fast clip in many organisations around the world. However, the transition towards Artificial Intelligence (AI) and machine learning technologies as supporting processes go at their own pace in other contexts beyond the US and Europe and cast doubts about their implementation. This article examines perceived ideas and problems about automation in Australian newsrooms. It investigates to what extent news professionals have undertaken the adoption of different automated tools in their work and the limits of using these technologies. This study stems from a broader research question focused on studying the evolution of automated decision-making systems (ADMS) in journalism in Australia and beyond. Preliminary findings suggest there is no singular approach to automation and there are contrasting views between those who believe ADMS will have a greater impact on the work and others who argue "AI will not replace human journalists in the near future". The COVID-19 pandemic accelerated interest in alternative automation processes.